Women’s waqfs in Islamic civilisation (İstanbul)
98 sayfa
Keywords: “This book results from research on the waqfs (charitable foundations-endowments) which were established and conducted by women in Muslim societies across history. The research which resulted in this book was undertaken by IRCICA principally with the aim of highlighting the role that women have played and the contributions they made to the promotion of charitable deeds and the development of economic and social activities in various sectors of life. The waqf institution, which is known to have originated in Islam, has provided a fruitful channel of social deeds for ladies from all spheres of society but naturally mostly those from ruling families, notable and well-to-do circles, through which they invested in benevolent action. The research was based on historical documents as well as history books. It is published in separate English, French and Arabic editions. It contains colour photographs of structures such as mosques, schools and fountains established by women in different countries“ -- “Bu eserde İslam medeniyetinin sosyal alandaki en önemli kurumlarından olan vakıf müesseselerinde kadınların rolü ele alınmaktadır. İslam tarihi boyunca Müslüman toplumlarda sosyal, iktisadi ve eğitim-bilim alanlarına çok önemli katkılarda bulunan vakıfların kurulmasında kadınların rolü büyük önem arz etmektedir. Tarihi belgelere ve kroniklere göre tamamen bilimsel olarak hazırlanmış bu eser, İslam tarihinde sosyal alanlarda kadınların yeri ve konumunu ortaya koymayı amaçlamaktadır“ --